Membrana transdérmica de liberação controlada utilizando quitosana, plasma e plaquetas para a regeneração de feridas - Alvarado, Leandro Garcia [UNESP] (2012)
The improvement of a formulation involves several important steps that range from knowledge of the characteristics of the inputs used, until proof that the application is safe for commercialization. The objective of this work is to study the use of chitosan and platelet concentrates CP in the repair of epithelial tissues mainly by chronic venous wounds. This will be produced transdermal membranes chitosan CP associated with the use of cross linking agents adsorbed at various concentrations. It is estimated that nearly 3% of the population suffer from this type of injury, which rises to 10% for diabetics, and that around 4 million people are suffering from chronic injuries or have some type of complication in the process healing. Search, therefore, new features and technologies that enable the population access to a treatment effective, efficient and low cost